On the classification of foliations of degree three with one singularity. (September 2022) - Coutinho, S.C.
Abstract: With the help of the Axiom computer algebra system we give a computer aided proof of the classification of foliations of the projective plane with only one singularity and finite non-trivial isotropy group and study their algebraic solutions.